Minimum Wages and Retirement - Mark Borgschulte; Heepyung Cho (Institute of Labor Economics (IZA), 2018)
We study the effect of the minimum wage on the employment outcomes and Social Security claiming of older US workers from 1983 to 2016. The probability of work at or near the minimum wage increases substantially near retirement, and previous researchers and policies suggest that older workers may be particularly vulnerable to any disemployment effects of the minimum wage. We find no evidence that the minimum wage causes earlier retirements. Instead, our estimates suggest that higher minimum wages increase earnings and may have small positive effects on the labor supply of workers in the key ages of 62 to 70. Consistent with increased earnings and delayed retirement, higher minimum wages decrease the number of Social Security beneficiaries and amount of benefits disbursed. The minimum wage appears to increase financial resources for workers near retirement.
Keywords: H55; J26; J38; J42; 330; minimum wage; retirement; social security claiming